PENGARUH PERAWATAN METODE KANGGURU TERHADAP TINGKAT KECEMASAN IBU DENGAN BAYI BERAT BADAN LAHIR RENDAH - Yuanita Syaiful; Lilis Fatmawati; Cicik Nurma Tristanti (STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Low Birth Weight (LBW) infants with weak clinical conditions and requiring treatment in an intensive room, separated from their mothers are a cause of anxiety in mothers. The kangaroo mother care provides an opportunity for the baby to attach to the mother to create a bounding attachment that gives the mother satisfaction. The purpose of this study was to explain the effect of kangaroo care on the anxiety level of mothers with low birth weight babies in the NICU. This study used a Pre Experimental One Group Pre Post Test Design without a control group. The population is mothers with low birth weight babies who are treated at Bhakti Dharma Husada Hospital Surabaya. A sample of 14 respondents was taken by purposive sampling, according to inclusion criteria. The independent variable is the kangaroo mother care and the dependent variable is the level of anxiety of mothers with LBW babies. Data were collected using the Hamilton Anxiety Rating Scale (HARS) questionnaire and the intervention was carried out 2 hours for 3 days. Data were analyzed using the Wilcoxon sign rank test with a significance level of <0.05. The results showed that the level of anxiety of mothers with low birth weight babies before the intervention was 78.57% moderate anxiety, while after the intervention was 85.72% mild anxiety. While the significance level = 0.001 which means that there is an effect of kangaroo mother care on the anxiety level of mothers with low birth weight babies. The kangaroo mother care can reduce anxiety so that it can be implemented in the hospital and later the mother can also continue on her own at home.